Human beta defensin-1 is involved in the susceptibility to adeno-tonsillar hypertrophy. - Zupin, Luisa; Celsi, Fulvio; Bresciani, Martina; Orzan, Eva; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2018)
INTRODUCTION: Innate immunity molecules are known to play a pivotal role in the homeostasis of the oral mucosa, permitting the presence of commensal microflora and, at the same time, providing a first line of defense against pathogens attempting to invade the oral cavity. Tonsils represent the local immune tissue in oral cavity, being able to provide a non-specific response to pathogens; however, in the presence of microbes or foreign materials present in the mouth tonsils could became infected and develop chronic inflammation, thus leading to hypertrophy. The etiology of the disease is multifactorial depending upon environmental and host factors, the latter including molecules of mucosal innate immunity. METHODS: Ninety-five children with adeno-tonsillar hypertrophy subjected to adeno-tonsillectomy were recruited at the pediatric otorhinolaryngology service of the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste (Italy). The specimen discarded from the surgery were used for genomic DNA extraction and genotyping, for mRNA extraction and gene expression analysis, finally the samples were cut and used to prepare slides to perform immunohistochemistry. RESULTS: Functional polymorphisms within DEFB1 gene, encoding the human beta defensin-1 (hBD-1), were analyzed finding association between DEFB1 rare haplotypes and susceptibility to adeno-tonsillar hypertrophy. DEFB1 mRNA expression was detected in the tonsils and the hBD-1 protein was localized at the epithelia of tonsils mainly in the proximity of the basal lamina. CONCLUSION: Our findings lead us to hypothesize an involvement of hBD-1 mediated innate immunity in the modulation of the susceptibility towards adeno-tonsillar hypertrophy development.
Keywords: Adenoidectomy; Adenoids; Adolescent; beta-Defensins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Hypertrophy; Immunity, Innate; Immunohistochemistry; Italy; Male; Palatine Tonsil; Tonsillectomy